Capacity for social contingency detection continues to develop across adolescence. Issue 3 (30th November 2021) - Hermans, Karlijn S. F. M.; Kirtley, Olivia J.; Kasanova, Zuzana; Achterhof, Robin; Hagemann, Noëmi; Hiekkaranta, Anu P.; Lecei, Aleksandra; Zapata‐Fonseca, Leonardo; Lafit, Ginette; Fossion, Ruben; Froese, Tom; Myin‐Germeys, Inez
Abstract: The capacity for dynamically coordinating behaviour is assumed to have largely matured in infancy. In adolescence—another sensitive period for social development—the primary focus on individual social cognition as the main driver of interaction has prevented the study of actual social interaction as behavioural coordination within dyads. From a dynamic perspective, however, capturing real‐time social dynamics is essential for the assessment of social interactive processes. In order to improve the understanding of social development during adolescence, we investigated the potential developmental course of social contingency detection in dynamic interactions. Pairs of 205 Belgian adolescents (83 male, 122 female), aged 11–19, engaged in real‐time social interaction via the Perceptual Crossing Experiment (PCE). Comparing early, middle and late adolescents, we found a generally higher performance of late adolescents on behavioural and cognitive measures of social contingency detection, while the reported awareness of the implicitly established social interaction was lower in this group overall. Additionally, late adolescents demonstrated faster improvement of behavioural social coordination throughout the experiment, compared with the other groups. Our results indicate that social interactive processes continue to develop throughout adolescence, which manifests as faster social coordination at the behavioural level. This finding underscores dynamic social interaction within dyads as a new opportunity for identifying altered social development during adolescence.